A study of the utility of lactate dehydrogenase, total proteins, and adenosine deaminase in the diagnosis of pleural exudates: A new statistical approach - Mihir Mehta,; Simbita Marwah,; Hitesh Shah,; Amit Trivedi, (Universiti Kebangsaan Malaysia, 2015)
Background: Pleural fluid (PF) may be transudative or exudative. Total protein estimation from PF is used to detect exudative pleural effusion. Objectives: To determine the role of new suggested criteria consisting of lactate dehydrogenase (LDH), total proteins (TP), and adenosine deaminase (ADA) in diagnosis of pleural effusion and differentiate it into transudative and exudative and also to compare it with Light’s criteria. Materials and Methods: This was a cross-sectional study comprising 101 patients with pleural effusion, classified by previously established criteria as transudates or exudates. The study was carried out in a 550-bedded tertiary-care, ruralbased, teaching hospital for 1 year. Diagnostic parameters mentioned in Light’s criteria were performed from PF and serum, whereas parameters of the new criteria used in our study (LDH, TP, and ADA) were performed from PF. Receiveroperating characteristic curve was used to determine the cutoffs, multiple parallel tests were applied to combine individual test markers to optimize diagnostic accuracy and sensitivity, and specificity and diagnostic accuracy for each test were calculated. Results: After using multiple parallel tests, the sensitivity, specificity, and accuracy of Light’s criteria for diagnosing exudates were 98.9%, 75%, and 95% and those for transudates were 95.29%, 80%, and 93%, respectively. Whereas for the proposed new criteria, sensitivity, specificity, and accuracy for diagnosing exudates were 98.81%, 93.75%, and 98% and those for transudates were 95.23%, 87.5%, and 94%, respectively. The accuracy of new criteria was comparable to that of Light’s criteria (p = 0.0018). Conclusion: From our study, it can be concluded that PF analysis of LDH, TP, and ADA has high sensitivity and specificity for diagnosing pleural effusions and can be used as useful markers to suggest exudative effusions.